The Effect of Workload on Employee Loyalty with Job Stress as a Moderating Variable at the Department of Manpower, Cooperatives, and Small and Medium Enterprises of Serdang Bedagai Regency - Muhammad Rifandi; Kiki Farida Ferine; Yohny Anwar (CV. Doki Course and Training, 2026)
This study aims to analyze the influence of compensation, workload, and work environment on the performance of Non-ASN employees at the Regional Asset Finance Agency of North Sumatra Province both partially and simultaneously. This type of research is quantitative research with a causal associative approach. The research population is all Non-ASN employees at BKAD North Sumatra Province which totals 54 people, and all of them are used as research samples using saturated sampling techniques (census). Data collection techniques were carried out through questionnaires and documentation studies. The data analysis technique used multiple linear regression analysis with the help of SPSS software. The results of the study showed that partially compensation had a positive and significant effect on employee performance with a t-value of 3.944 and a significance of <0.001, workload had no significant effect on employee performance with a t-value of 1.644 and significance of 0.106, and the work environment had a positive and significant effect on employee performance with a t-value of 4.161 and significance <0.001. The work environment is the most dominant variable affecting employee performance with a Beta coefficient of 0.411. Simultaneously, compensation, workload, and work environment had a significant effect on employee performance with an F value of 59.496 and a significance of <0.001. The determination coefficient (R²) of 0.781 showed that 78.1% of the variation in the performance of Non-ASN employees could be explained by three independent variables, while the remaining 21.9% was explained by other variables outside this study.